AUDITOR INDEPENDENCE AND EARNINGS MANAGEMENT: EVIDENCE OF NON-AUDIT FEES DISCLOSURE IN AUSTRALIA - Rusmin; Van der Zahn, J-L.W. Mitchell; Tower, Greg; Brown, Alistair (The journal of contemporary issues in business and government, 2009)
This study examines the association between the magnitude of earnings management and auditor independence of 325 Australian listed firms. Auditor independence is the epicentre of this study’s analysis as this factor is considered to be a key determinant of earnings management. Our findings indicate the lack of a universal association between auditor independence and earnings management attributes. The main result is supported by tests using alternative measures of auditor independence. This result suggests that the provision of non-audit services by the incumbent auditor does not compromise independence. New regulatory initiatives, such as the Australian CLERP 9 law reforms, are thus queried.